Chapter La filosofia politica della speranza. Appunti sull'eredità intellettuale di Sergio Caruso - Spini, Debora (Studi e saggi, 2023)
This chapter summarises the main lines of Caruso's philosophical work. First of all, my chapter will engage with Caruso's epistemological reflection, with a special focus on Philosophy of Social Sciences; it will then move on to touch on other aspects, such as the critique to capitalism - which led him to a wider reflection on philosophy of economics - and the constant dialogue with Jewish philosophy and theology. After short analysis of his work on citizenship, my chapter will close by sketching a few possible scenarios to preserve Caruso's intellectual legacy.